Inhaled nitric oxide for pulmonary hypertension after repair of exomphalos. Issue 5 (November 1993) - Miller, O I; Gaynor, J W; Macrae, D J; Tasker, R C
Abstract : Inhaled nitric oxide was used successfully to treat a newborn infant with severe pulmonary hypertension complicating repair of congenital exomphalos. The infant had failed conventional treatment and extracorporeal membrane oxygenation was unsuitable because of the risk of bleeding from the recent laparotomy. Extended treatment with inhaled nitric oxide appears safe and may offer an alternative to mechanical life support in severe cases of neonatal pulmonary hypertension.